2020
DOI: 10.1002/suco.201900228
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of multiscale hybrid fiber reinforced cementitious composites under single degree of freedom hydraulic shaking table

Abstract: Recently, the multiscale hybrid fiber reinforced cementitious composites (MSHyFRCC) with steel fibers, polyvinyl alcohol (PVA) fibers, and calcium carbonate whiskers had developed with improved mechanical properties under static load. Although, there is still a research gap to study its behavior and properties under the action of earthquake load. In this work, the properties of steel fibers, PVA fibers, and calcium carbonate whisker hybrid FRCC are evaluated by using single degree of freedom hydraulic shaking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 47 publications
1
38
0
Order By: Relevance
“…Variables for UHSC include the cement content, the water content, the additive material content, the fiber content (e.g., steel fibers), the content and type of admixtures, and aggregates content and type (e.g., superplasticizer) [ 5 , 6 , 7 ]. The addition of dispersed short-discrete fibers to concrete increased crack resistance and improved mechanical characteristics [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Steel fibers are employed to increase the toughness and post-cracking behavior of the cementitious material [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Variables for UHSC include the cement content, the water content, the additive material content, the fiber content (e.g., steel fibers), the content and type of admixtures, and aggregates content and type (e.g., superplasticizer) [ 5 , 6 , 7 ]. The addition of dispersed short-discrete fibers to concrete increased crack resistance and improved mechanical characteristics [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Steel fibers are employed to increase the toughness and post-cracking behavior of the cementitious material [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 The fibers in concrete restricted the crack propagation, crack extension and resulted in more strain capacity than that of PC. [2][3][4][5][6][7] The compressive stress-strain response is as an important factor for the evaluation of toughness level. 8 Furthermore, hybrid fiber reinforced concrete (HyFRC) was used to achieve an efficient improvement in the compressive behavior as well as the crack resistance from micro to macro-level.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of fibers in plain concrete (PC) played an important role in the post‐peak response of compressive stress–strain curve 1 . The fibers in concrete restricted the crack propagation, crack extension and resulted in more strain capacity than that of PC 2–7 . The compressive stress–strain response is as an important factor for the evaluation of toughness level 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that the addition of fibers is an effective way to improve the strength of composites [ 20 , 21 , 22 ]. The application of hybrid fibers in cement matrix composites in the construction industry has gained considerable developments during past the few decades [ 23 , 24 , 25 , 26 , 27 ]. Steel fibers showed higher thermal conductivity and thermal stability with crack resistance phenomena against thermal stress, even under high temperatures because of effective heat transfer phenomena.…”
Section: Introductionmentioning
confidence: 99%